1(t-6)+7t=4(2t+5)-8

Simple and best practice solution for 1(t-6)+7t=4(2t+5)-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1(t-6)+7t=4(2t+5)-8 equation:


Simplifying
1(t + -6) + 7t = 4(2t + 5) + -8

Reorder the terms:
1(-6 + t) + 7t = 4(2t + 5) + -8
(-6 * 1 + t * 1) + 7t = 4(2t + 5) + -8
(-6 + 1t) + 7t = 4(2t + 5) + -8

Combine like terms: 1t + 7t = 8t
-6 + 8t = 4(2t + 5) + -8

Reorder the terms:
-6 + 8t = 4(5 + 2t) + -8
-6 + 8t = (5 * 4 + 2t * 4) + -8
-6 + 8t = (20 + 8t) + -8

Reorder the terms:
-6 + 8t = 20 + -8 + 8t

Combine like terms: 20 + -8 = 12
-6 + 8t = 12 + 8t

Add '-8t' to each side of the equation.
-6 + 8t + -8t = 12 + 8t + -8t

Combine like terms: 8t + -8t = 0
-6 + 0 = 12 + 8t + -8t
-6 = 12 + 8t + -8t

Combine like terms: 8t + -8t = 0
-6 = 12 + 0
-6 = 12

Solving
-6 = 12

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 7d-3=5d-9 | | 20-x=3(x+4) | | 5(-12-6)+2=7(-12)-4 | | 0.6t+0.4=2 | | x^4-8x^2=-12 | | 12+2=7(3-y) | | -(8y+2)-(7y-8)=-2 | | (3x+9)+6x=180 | | 3x^2+16x-64=0 | | 5(x+7)=6(x-15) | | 6(v-2)=2v-4 | | 3.2q-4.6-5.9q=1.7q-4.6 | | 5=4(x+2)-n | | 0.6d-0.04+0.2d=0.12 | | w-4=-14 | | 0.6d-0.04*0.2d=0.12 | | 2x+0.5x=y | | 5a-3b-1=0 | | 5(x-6)+2=7x-4 | | 9x^2+27X+54=540 | | 9x^1+27x+54=540 | | 0.25x=-5 | | 6(x-2)=2(9x-2) | | 0=120x-x^2 | | -0.6x=0.45 | | -3m^2+6m+24=0 | | 0=210x-x^2 | | x-7.8=-3.3 | | x+(x+1)+x+2=33 | | 60=64x-16x^2 | | 4m-9=27 | | x+(x+2)+x+4=54 |

Equations solver categories